2018
DOI: 10.1111/jcpt.12661
|View full text |Cite
|
Sign up to set email alerts
|

Dosing oxaliplatin in a haemodialysis patient with metastatic rectum cancer monitored by free platinum concentrations

Abstract: Dosing oxaliplatin in a haemodialysis patient monitored by free platinum concentrations was effective, safe and feasible in clinical practice. Further research is needed to determine the best pharmacokinetic parameter or combination of parameters and corresponding target values to further optimize the oxaliplatin dose for the individual haemodialysis patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Table 1 lists the published cases involving FOLFOX therapy for colorectal cancer in patients receiving chronic hemodialysis [4, 5, 6, 7, 8, 9, 10, 11, 12, 13]. In all listed cases, the L-OHP dose was reduced to 50–80% of the standard dose (85 mg/m 2 ) and in most, hemodialysis was initiated immediately after L-OHP infusion.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Table 1 lists the published cases involving FOLFOX therapy for colorectal cancer in patients receiving chronic hemodialysis [4, 5, 6, 7, 8, 9, 10, 11, 12, 13]. In all listed cases, the L-OHP dose was reduced to 50–80% of the standard dose (85 mg/m 2 ) and in most, hemodialysis was initiated immediately after L-OHP infusion.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Oxaliplatin is a platinum drug that is mainly secreted from the kidney and, therefore, generally contraindicated in patients with severe renal impairment. Pharmacokinetic studies have revealed no accumulation of free platinum detectable in patients with hemodialysis (8). The FOLFOX regimen, which includes a dose of 70 mg/m 2 oxaliplatin, is effective and safe in colorectal cancer patients with hemodialysis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies have revealed no accumulation of free platinum detectable in patients with hemodialysis (8). The FOLFOX regimen, which includes a dose of 70 mg/m 2 oxaliplatin, is effective and safe in colorectal cancer patients with hemodialysis (8). Based on these previous and present findings, we conclude that a half-dose of the CapeOX regimen is optimal for gastric cancer patients on hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] To date, only a few case reports of dosing oxaliplatin in hemodialysis patients have been published. [3][4][5][6][7] In this study, we report the case of a hemodialysis patient with metastatic colon cancer who was safely treated with FOLFOX therapy by monitoring total and free platinum concentrations in plasma.…”
Section: Introductionmentioning
confidence: 99%